2013
DOI: 10.2478/s13386-013-0130-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of cathodoluminescence of alkali feldspar to He+ ion implantation and electron irradiation

Abstract: Cathodoluminescence (CL) of minerals such as quartz and zircon has been extensively studied to be used as an indicator for geodosimetry and geochronometry. There are, however, very few investigations on CL of other rock-forming minerals such as feldspars, regardless of their great scientific interest. This study has sought to clarify the effect of He + ion implantation and electron irradiation on luminescent emissions by acquiring CL spectra from various types of feldspars including anorthoclase, amazonite and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Similar phenomenon has been also observed in annealing experiments of highly metamict zircon (Nasdala et al, 2002). Kayama et al (2013) also demonstrated a similar reduction of emission intensity accompanied with a decrease in crystallinity of feldspars by He + ion implantation, which is caused by the ionization effect, the luminescence quenching or lowering of luminescence efficiency due to a change in activation energy associated with hopping between adjacent channels, as suggested by Curie (1963), Brooks et al (2001) and King et al (2011). Similar reduction of the luminescence efficiency has been also found in CL of quartz (King et al, 2011).…”
Section: Narrow Emission Peakssupporting
confidence: 67%
“…Similar phenomenon has been also observed in annealing experiments of highly metamict zircon (Nasdala et al, 2002). Kayama et al (2013) also demonstrated a similar reduction of emission intensity accompanied with a decrease in crystallinity of feldspars by He + ion implantation, which is caused by the ionization effect, the luminescence quenching or lowering of luminescence efficiency due to a change in activation energy associated with hopping between adjacent channels, as suggested by Curie (1963), Brooks et al (2001) and King et al (2011). Similar reduction of the luminescence efficiency has been also found in CL of quartz (King et al, 2011).…”
Section: Narrow Emission Peakssupporting
confidence: 67%